Genomic Insights Into the Molecular Basis of Sexual Selection in Birds - Jaiswal, Shubham K.; Gupta, Ankit; Shafer, Aaron B. A.; P. K., Vishnu Prasoodanan; Vijay, Nagarjun; Sharma, Vineet K. (Frontiers in Ecology and Evolution, 2021)
Sexual selection is a well-known biological process, yet the genomic basis and patterns of sexual selection are not fully understood. The extravagant ornamental plumage of peacock (Pavo cristatus) was instrumental in shaping Charles Darwin’s theory of sexual selection and is considered to be an honest signal of its immunocompetence. Here, we used the recently generated draft genome sequence of peafowl (Pavo cristatus) and carried out a comparative analysis across eleven bird genomes that encompass a range of sexual selection and also had high-quality genomic and phenotypic data publically available to study the genomic basis of sexual selection. We found that varying degree of purifying selection was the predominant mechanism of action for sexual selection at the genome-wide scale and observed that sexual selection mostly influences genes regulating gene expression and protein processing. Specifically, the genome-wide phylogenetically corrected regression analysis supported the continuous or ongoing model of sexual selection. Genes involved in nucleic acid binding and gene expression regulation, including a specific regulator of sex-determination known as TRA2A to be under positive selection in the species with high postcopulatory sexual selection manifested as high sperm competition. We also detected specific feather-related and immune-related gene-pairs evolving under similar selection pressures across the eleven species, including peacock (Pavo cristatus), which is consistent with the Hamilton-Zuk hypothesis. The comparative genomics analysis of eleven avian taxa has provided new insights on the molecular underpinnings of sexual selection and identifies specific genomic regions for future in-depth analysis.